Estrés y burnout docente: conceptos, causas y efectos - Zavala Zavala, José (2008)
In this article the concepts of stress (eustress and distress) and stress coping arereviewed under a transactional perspective mainly, and it is also described the burnoutor syndrome of professional wearing as consequence of the chronic stress. Itis also offered a series of statisticals related to Latin-American teachers’ perceptionsof stress and health conditions, and there is indeed the shadow of a doubt of thepossible suffering of burnout. The stress has direct effects in the physical and psychologicalwell being of the teacher, and simultaneously an impact in the personallife and his/her performance of the educational organization.